Level of job satisfaction and its associated factors among midwives working in public health institutions, Northwest Ethiopia: a multi-center study - Nebiyu Solomon Tibebu; Berihun Agegn Mengistie; Saron Abeje Abiye; Paulos Abeje; Selamawit Tilahun; Sosina Belay; Geremew Azene; Belayneh Ayanaw Kassie (BMC Research Notes)
Abstract Introduction Midwives are practitioners of midwifery and are recognized as indispensable professionals for lowering maternal mortality worldwide, particularly in low-income countries. Midwives who aren’t satisfied with their job challenge the prevention and control of maternal mortality and morbidity and had a surge in unfavorable patient outcomes. Therefore, this study aimed to assess the level of job satisfaction and its associated factors among midwives working at public health institutions in northwest Ethiopia. Methods An institutional-based cross-sectional study was conducted from February 1st to July 15th, 2022. A total of 422 midwives participated in the study. A simple random sampling method was used to select all eligible participants. Data were collected using a semi-structured, pretested, and self-administered questionnaire. Data version 4.6 software and SPSS 25 were used for data entry and analysis, respectively. Both bivariable and multivariable logistic regression analyses were conducted to find factors associated with midwives’ job satisfaction. The statistical association was decided based on the adjusted odds ratio (AOR) with its 95% confidence interval (CI) and p-value of < 0.05. Results The prevalence of midwives’ satisfaction with their job was 46.7% (95% CI: 41.8, 52.0). Institutions followed democratic leadership (AOR = 2.03, 95% CI: 1.02, 4.40), having good relationships with their superiors (AOR = 2.01, 95% CI: 1.00, 5.02), being satisfied with payment and benefits (AOR = 4.00, 95% CI: 1.45, 9.12), and safe job security (AOR = 5.66, 95% CI: 4.8, 12.68) were found to be statistically significant factors associated with midwives’ job satisfaction. Conclusion and recommendations In this study the level of midwives’ job satisfaction was low. Thus, setting strategies in exercising democratic leadership, promoting good relations with superiors, providing incentives opportunities, and ensuring work security will have significant role in improving midwives’ satisfaction with their job.